Anaplastic Large Cell Lymphoma Presenting as Ulcerative Facial Mass: : A Case Report - Akpunonu, Basil (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.